AKUNTABILITAS DALAM PENGAWASAN PENYALURAN PERUMAHAN SUBSIDI DAN TINGKAT KETEPATAN SASARAN PENERIMA RUMAH SUBSIDI DI KOTA PALANGKA RAYA - Sari, Mita; Akhmad, Beni; Kumalasari, Desy (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
Abstract-This research aims to determine the accountability of supervising the distribution of subsidized housing and the accuracy of its targets in Palangka Raya City. The research approach used is of a qualitative type using service quality theory, accountability theory and public policy theory and data collection techniques through observation, interviews and documentation. The results of the study indicate that the function of supervising the distribution of subsidized housing in Palangka Raya City is carried out directly by the central government without involving local government, it then becomes one of the factors causing the lack of accuracy in the distribution of targets because there is no supervisory function from the local government or local provincial government. The lack of strict supervision of channeling banks is also one of the factors causing the government's lack of accountability in supervising the distribution itself, infrequent inspections or checks in the field also lead to deviations from the recipients of subsidized housing such as houses that are not occupied until they are transferred or rented to third parties, which of course violates existing regulations, indicators of accountability in the implementation of the distribution of subsidized housing have been fulfilled but are still not optimal considering that aspects of supervision and accountability are actually held by the implementing bank in an area for distributing subsidized housing.Keywords:   Supervision Accountability, Subsidized housing-Abstrak-Penelitian ini bertujuan untuk mengetahui akuntabilitas pengawasan penyaluran rumah subsidi dan ketepatan sasarannya di Kota Palangka Raya. Pendekatan penelitian yang digunakan adalah tipe kualitatif dengan menggunakan teori kualitas pelayanan, teori akuntabilitas dan teori kebijakan publik serta teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa fungsi pengawasan pendistribusian rumah subsidi di Kota Palangka Raya dilakukan langsung oleh pemerintah pusat tanpa melibatkan pemerintah daerah, hal tersebut kemudian menjadi salah satu faktor penyebab kurang tepatnya dalam pendistribusian target. karena tidak ada fungsi pengawasan dari pemerintah daerah atau pemerintah provinsi setempat. Kurangnya pengawasan yang ketat terhadap bank penyalur juga menjadi salah satu faktor penyebab kurangnya akuntabilitas pemerintah dalam mengawasi penyaluran itu sendiri, jarangnya pemeriksaan atau pengecekan di lapangan juga menyebabkan terjadinya penyimpangan dari penerima rumah subsidi seperti rumah yang tidak ditempati. sampai dialihkan atau disewakan kepada pihak ketiga, yang tentunya menyalahi peraturan yang ada, indikator akuntabilitas dalam pelaksanaan penyaluran rumah subsidi sudah terpenuhi namun masih belum optimal mengingat aspek pengawasan dan pertanggungjawaban benar-benar dipegang oleh pelaksana. bank di kawasan penyaluran perumahan subsidi.Kata kunci: Akuntabilitas Pengawasan, Perumahan Subsidi